Effect of the side chain spacer structure on the pH-responsive properties of polycarboxylates. Issue 10 (13th August 2017) - Harada, Atsushi; Teranishi, Ryoma; Yuba, Eiji; Kono, Kenji
Abstract: The properties of stimuli-responsive polymers change significantly with changes to their environment, such as temperature and pH. This behavior can be utilized for the preparation of stimuli-responsive carriers for efficient cytosolic delivery of active drugs. Among the possible environmental conditions, pH is one of the most useful stimuli because the pH in an endosome is lower than under physiological conditions, depending on endosomal development. This pH difference is an important factor in the design of pH-responsive polymers, which can be used to enhance the transport of endocytosed drugs from the endosomal compartment to the cytoplasm. Such polymers can destabilize the endosomal bilayer under mildly acidic conditions and be nondisruptive at pH 7.4 not only for efficient endosomal escape but also for the suppression of nonspecific interaction with lipids existing under physiological conditions. In this study, we developed polycarboxylates with well-controlled pH-responsive properties bearing various spacer structures with different hydrophobicity. 3-methyl glutarylated polyallylamine and 2-carboxy-cyclohexanoylated polyallylamine were synthesized through the reaction between primary amine of PAA and acid anhydrides. Side chain spacers with higher hydrophobicity induced significant interactions with liposomal membranes at higher pH. pH-destabilizing liposomes could be modulated through the changing the composition of spacer structures with different hydrophobicity. Such formulations may represent an attractive strategy for the improvement of cytosolic delivery of active molecules.